2014
DOI: 10.21307/sjcapp-2015-018
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Personality Disorders and Quality of Life in Adolescent Outpatients

Abstract: Background: During recent years, there has been an increasing focus on the benefits of the early detection and treatment of personality disorders in adolescents. Previous studies of adults have shown that the number of personality disorder criteria met is negatively correlated with a patient's quality of life and general functioning. Objective: The aim of the present study was to investigate the prevalence of personality disorders, particularly with regard to the correlation between the number of personality d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 41 publications
0
9
0
1
Order By: Relevance
“…This left 201 adolescents eligible for inclusion in the study. The attrition was 48 (23.9 %); lack of consent from parents (N = 5, 10.4 %), referral retracted prior to interview (N = 6, 12.5 %), lack of consent from the adolescent (N = 7, 14.6 %), did not show up for appointment (N = 11, 22.9 %), and consent retracted during interview (N = 19, 39.6 %) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This left 201 adolescents eligible for inclusion in the study. The attrition was 48 (23.9 %); lack of consent from parents (N = 5, 10.4 %), referral retracted prior to interview (N = 6, 12.5 %), lack of consent from the adolescent (N = 7, 14.6 %), did not show up for appointment (N = 11, 22.9 %), and consent retracted during interview (N = 19, 39.6 %) [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…All referred patients in the study’s age group were asked to participate. Exclusion criteria were the need for immediate hospitalization or other urgent therapeutic measures, clinically assessed mental retardation, lack of fluency in the Norwegian language, and absence of the evaluator at the time of referral [ 44 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, studies have found a linear relationship between the number of BPD criteria met and the actual dysfunction and reduction in quality of life with higher numbers of BPD criteria met implying poorer functioning and greater reduction in quality of life . The effects of a personality disorder on functioning and quality of life may be even worse when a comorbid axis I disorder is diagnosed .…”
Section: Introductionmentioning
confidence: 99%
“…The symptoms may seem consistent with the typical adolescence features but can be clearly distinguished from these by its severe, pervasive and persistent nature. Although often examined in isolation, major depressive disorder (MDD) shows a high level of co-morbidity with a range of PDs, especially BPD [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies indicated that as many as 25% of adolescents treated in mental health outpatient clinics meet the diagnostic criteria for borderline personality disorder (BPD) alone, rising to 49% in inpatient units [ 13 , 15 , 20 ]. A study of unselected adolescents referred to a non-specialized mental health outpatient clinic showed that 22% of the referred adolescents had at least one PD, with cluster B (i.e., mainly borderline) and cluster C (i.e., mainly avoidant and dependent) being the most prevalent PDs [ 11 ]. Hence, the distribution of PDs among adolescents did not differ from the distribution found in equivalent adult samples.…”
Section: Introductionmentioning
confidence: 99%